Model Pemantauan Keamanan Jaringan Melalui Aplikasi Telegram Dengan Snort - Natanael Christianto; Wiwin Sulistyo (Maranatha University Press, 2021)
Network security is the main of the development of today's technology. The ease in accessing the internet also requires protection on users is required. The ease of accessing the internet by people can also cause the occurrence of cyber crime. Cyber crime can be done by all internet users, without exception, to earn a profit. Security monitoring system server through the app messenger Telegram can help administrators in the work because always be on standby in front of the server computer. Notice of Snort as IDS via Telegram also quicked and can be accepted anywhere. In taking action when the server something happened not too late. Target cyber crime also can attack anyone without exception. A system should be a strength, with the protection of a secure network that will be difficult to hack by hackers. The server is the main target in the conduct of cyber crime. The use of the server must maintain to secure all the data is not misused by persons who are not responsible. Each server is a system that should be an administrator as a guard on duty watching and taking action when something happens on the server. To monitor a server, an administrator should always standby in front of the server computer so as not to late take action when the server is about to happen something.